Effusive Constrictive Pericarditis in the Era of COVID-19 - Shriya Sharma; Si Pham; Archer Martin; Jose Ruiz; Caitlyn Luce; Aarti Desai; Rohan M. Goswami (Annals of Internal Medicine: Clinical Cases)
Effusive-constrictive pericarditis is a rare condition in which the visceral pericardium compresses the heart, with fluid accumulation in the pericardial space leading to cardiac tamponade. We present a case of 59-year-old man with effusive-constrictive pericarditis that was refractory to standard therapy. The symptoms appeared after he received a Moderna COVID-19 booster, with electrocardiogram findings showing PR depression and ST-segment elevation and cardiac imaging findings revealing abnormalities including thickened pericardium, ventricular interdependence, and septal bounce. Given the patient's abnormal hemodynamics and intolerance to high-dose nonsteroidal anti-inflammatory drugs, he was prescribed rilonacept. Because of the recalcitrant nature of his disease, pericardial stripping was done to prevent worsening of heart failure.